Urban Eye: Manhole Surveillance with IoT - Anusha N; Girijamba D.L.; Pooja; Preethu S; Niveditha V. (International Journal of Machine Systems and Manufacturing Technology, 2023)
Every nation hopes to implement the idea of the "smart city" on its own. Many different issues must be resolved in order to grow the seed into a large tree. The drainage system is one of them, and it is essential. With the right drainage system, even a tiny region can make a significant contribution to society. A sewer system can be accessed through manholes. Manholes are the best approach to access the underground pipes if there are any obstructions in the drainage systems. If the obstructions are not removed, the sewage water would overflow by way of drains, which will aggravate both cars and residents. Even inclined manhole lids pose risks as they contribute to accidents. Moreover, the safety of sanitation workers entering these manholes is compromised due to a lack of awareness regarding the toxicity levels of sewage or drainage water. Although remedies for these issues exist, they rely on the initiative of authorities. The challenge lies in alerting the authorities to these problems promptly. This is precisely where our proposed system comes into play. By employing advanced sensors, we can continuously monitor the sewage water levels beneath the manhole covers. When these levels surpass a predefined threshold, an automatic alert is dispatched to the relevant authorities. The appropriate authorities receive fast updates as the condition of the manhole cover and the toxicity of the drainage water are thoroughly tracked simultaneously. To keep the general public informed about the status of these manholes, we have developed a user-friendly application. Through this app, individuals can access real-time information about the conditions of manholes nearby them.
Keywords: Authorities; GSM; Manhole; Scavengers; Sewage